Comparison of swept-source and enhanced depth imaging spectral-domain optical coherence tomography in quantitative characterisation of the optic nerve head. Issue 3 (13th June 2016) - Li, Dejiao; Taniguchi, Elise V; Cai, Sophie; Paschalis, Eleftherios I; Wang, Haobing; Miller, John B; Turalba, Angela V; Greenstein, Scott H; Brauner, Stacey; Pasquale, Louis R; Shen, Lucy Q
Abstract : Aims: To compare swept-source optical coherence tomography (SS-OCT) and enhanced depth imaging spectral-domain OCT (EDI-OCT) in quantitative assessment of optic nerve head (ONH) parameters. Methods: In a cross-sectional study, patients with primary open angle glaucoma (POAG) and age-matched control subjects underwent SS-OCT and EDI-OCT B-scans of the ONH in a single visit. Two masked readers independently measured the horizontal and vertical lamina cribrosa depth (LCDH and LCDV, respectively), as well as thinnest Bruch's membrane opening minimum rim width (BMO-MRW) from SS-OCT and EDI-OCT scans. We assessed agreement between SS-OCT and EDI-OCT measurements by linear regression models, Bland-Altman analysis and concordance correlation coefficients (CCC). Intrareader and inter-reader reproducibility was assessed using intraclass correlation coefficients (ICC). Results: One eye from each of 40 patients with POAG and 20 controls were included. All three ONH measurements were higher on SS-OCT than on EDI-OCT, with significant differences in LCDH (mean difference=31.7 µm, p<0.01) and thinnest BMO-MRW (mean difference=20.5 µm, p<0.01). Linear regression models described the agreement between SS-OCT and EDI-OCT measurements with R 2 >0.8 for LCDH among both patients with POAG and controls and for thinnest BMO-MRW among patients with POAG. The CCC was >0.8 overall for each parameter. Intrareader and inter-reader ICCs were ≥0.989 and ≥0.964, respectively, for all parameters. Conclusions: LCDH, LCDV and thinnest BMO-MRW measurements are not interchangeable between SS-OCT and EDI-OCT, but show good intrareader and inter-reader reproducibility and interdevice agreement for quantitative characterisation of the ONH, particularly among patients with glaucoma.